Malaysia's services industry towards the global environment - Lo, Bryan Ching Wing; Ooi, Ai Yee (2007)
Nowadays, services sector is an important engine of the global economy development and it continues to grow vigorously. The progress of globalization, government liberalization, and the rapid advancement of information and communication technology (ICT) contributes to the continual acceleration of this sector. Since the services sector is playing its role fruitfully as one of the main economic builders to many economies throughout the world, most governments are putting greater emphasis on services sector in their countries’ economic planning. Therefore, this paper describes briefly the evolution of services sector in Malaysia, the services world trade and the current global trend in this outstanding sector. Despite all the potential opportunities that the services sector would generate, the multifaceted challenges will be invoked simultaneously. Hence, this paper also will describe in broad the opportunities and challenges, which services sector will stimulate for service industry players specifically Malaysia. To survive in the dynamic and competitive service environment, there is an ultimate necessity for services players to build a competitive edge. At the end of the paper, three competitive service strategies namely positioning, people, and system is discussed.